Menstrual irregularity: a possible clinical marker of metabolic dysfunction in women with class III obesity - Souza, F. A. C. [UNESP]; Dias, Rogerio [UNESP]; Fernandes, C. E.; Pimentel, F.; Dias, D. [UNESP] (Informa Healthcare, 2010)
Purpose. To evaluate whether menstrual irregularity in morbidly obese women is indicative of metabolic dysfunction.Patients and Methods. Fifty-seven women with morbid obesity were evaluated. They were divided into two groups: one comprising women without menstrual dysfunctions or hirsutism (Group 1), and another obese women showing menstrual dysfunction with or without hirsutism (Group 2). The following were evaluated: age, colour, childbirth, marital status, profession, socio-economic level, education, age at menarche, body weight, height, body mass index, presence of hirsutism (Ferriman Gallwey Index), abdominal circumference, hip circumference, waist-to-hip ratio, menstrual cycle, blood pressure, presence of acanthosis nigricans, insulin resistance (IR), fasting glycaemia, total cholesterol, HDL-C, LDL-C, triglycerides, thyroid-stimulating hormone, free T4, luteinising hormone (LH), follicle-stimulating hormone, prolactin, total testosterone, dehydroepiandrosterone sulfate, insulin and the Homeostasis Model Assessment (HOMA test).Results. Clinical and epidemiological aspects did not present statistical differences. Clinical and laboratory parameters did not show statistically significant alterations; however, HOMA test values for Group 2 were significantly higher than those for Group 1.Conclusions. The presence of IR in class III obese women can cause menstrual dysfunctions such as amenorrhoea or oligomenorrhoea even in the absence of hyperandrogenism, suggesting that IR plays an important role in the ovarian mechanisms involved in the menstrual cycle control.
Keywords: Class III obesity; morbid obesity; hypothalamic-hypophyseal-gonadal axis; hyperandrogenism